Community and Local Governance in Australia - Paul Smyth, Tim Reddel and Andrew Jones (A UNSW Press, 2005)
The contributions collected in this volume result from an Australian Research Council project initiated in 2001 by the School of Social Work and Applied Human Sciences of the University of Queensland in collaboration with the Queensland Government departments of the Premier and Cabinet, and Families. The research project was initiated because of the editors’ interest in examining the upsurge of spatially based policy activity aimed at addressing the spatial disadvantage that occurred in Queensland in the latter 1990s. The project’s examination over three years of the Queensland experience also highlighted similar policy initiatives in other Australian States. These developments mirrored global trends. Globalisation has accentuated uneven regional economic development, and governments throughout the world are seeking new policy directions to address the needs of people and communities excluded from the benefits and opportunities of citizenship by virtue of where they live. This book builds on the project’s three years of research activity, which included a series of policy forums culminating in a major symposium conducted in Brisbane during late 2003, in which leading national and international scholars and policy practitioners examined these trends from national and international perspectives. The book’s key theoretical themes and content areas were debated and developed during this symposium. Most of the chapters in this volume are based on papers given at that symposium. They have been selected from those presented and rewritten for publication. The research project could not have occurred without the efforts of many groups and people. Financial support from the Australian Research Council and the Queensland Government was of course crucial to the project. Staff from the School of Social Work and Applied Human Sciences at the University of Queensland and officials from a range of Queensland Government agencies, particularly the Departments of the Premier and Cabinet, and Families, supported the project from its inception, and many participated actively in the provision of administrative support, the development of research papers, and the planning and conduct of policy forums. In particular, Bob Stimson fulfilled his role as an associate investigator for the project with great enthusiasm and scholarship, and contributed significantly to the project team. Christine Nolan and Robert Bush offered many important policy insights and provided a pathway for Queensland Government agencies to allow access to key policy and program data for the project. Alice Thompson provided welcomed editorial assistance in the final stages of the production of the book’s manuscript. To all of them our grateful thanks